2009
DOI: 10.1113/jphysiol.2009.179226
|View full text |Cite
|
Sign up to set email alerts
|

Laminin enhances β2‐adrenergic receptor stimulation of L‐type Ca2+ current via cytosolic phospholipase A2 signalling in cat atrial myocytes

Abstract: We previously reported that attachment of atrial myocytes to the extracellular matrix protein laminin (LMN), decreases adenylate cyclase (AC)/cAMP and increases β 2 -adrenergic receptor (AR) stimulation of L-type Ca 2+ current (I Ca,L ). This study therefore sought to determine whether LMN enhances β 2 -AR signalling via a cAMP-independent mechanism, i.e.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 40 publications
2
15
1
Order By: Relevance
“…CytoD has been reported to interfere with multiple signaling pathways, though not with baseline Ca 2+ handling, 51 and effects of CytoD are mostly assigned to its action on the cytoskeleton. We currently do not have complementary tools for studying the role of the cytoskeleton, because, for example, colchicine reportedly affects baseline Ca 2+ transport.…”
Section: Limitationsmentioning
confidence: 99%
“…CytoD has been reported to interfere with multiple signaling pathways, though not with baseline Ca 2+ handling, 51 and effects of CytoD are mostly assigned to its action on the cytoskeleton. We currently do not have complementary tools for studying the role of the cytoskeleton, because, for example, colchicine reportedly affects baseline Ca 2+ transport.…”
Section: Limitationsmentioning
confidence: 99%
“…For specific stimulation of ␤ 1-AR-dependent signaling (␤ 1-AR stimulation), cells were treated with ISO (0.1 M) in combination with the ␤ 2-AR subtype blocker ICI-118,551 (0.01 M). Simultaneous activation of ␤ 2/Gi and ␤2/Gs signaling (␤2-AR stimulation) was achieved with the combination of ISO (0.1 M) and the specific ␤ 1-AR inhibitor atenolol (0.01 M), whereas for selective ␤ 2/Gs stimulation, fenoterol (41,42) was used (0.1 M). Concentrations were chosen based on our previous studies (10, 51) on ␤-AR signaling in cat atrial myocytes.…”
mentioning
confidence: 99%
“…Cell attachment to LMN decreases β 1 -AR signaling by inhibiting adenylate cyclase activity and diminishing cAMP levels via integrin-dependent activation of focal adhesion kinase (FAK)/phosphatidyinositol-3’ kinase (PI-3K)/protein kinase B (Akt) signaling [2]. We also reported that atrial cell attachment to LMN enhances β 2 -AR signaling by activating Gi/ERK/cytosolic phospholipase A 2 (cPLA 2 )/arachidonic acid (AA) stimulation of I Ca,L [ 3 ]. β 2 -AR activation of cPLA 2 signaling is dependent on concomitant LMN-mediated inhibition of adenylate cyclase/cAMP-dependent kinase (PKA) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also reported that atrial cell attachment to LMN enhances β 2 -AR signaling by activating Gi/ERK/cytosolic phospholipase A 2 (cPLA 2 )/arachidonic acid (AA) stimulation of I Ca,L [ 3 ]. β 2 -AR activation of cPLA 2 signaling is dependent on concomitant LMN-mediated inhibition of adenylate cyclase/cAMP-dependent kinase (PKA) [ 3 ]. In other words, cell attachment to LMN acts via inhibition of adenylate cyclase/PKA to both inhibit β 1 -AR signaling and enhance β 2 -AR signaling through activation of cPLA 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation